Description of the profasic chromosome in Meiosis I of Bostryx conspersus - Siles-Vallejos, María (2011)
Bostryx is among the most diverse genera within the Orthalicidae (Gastropoda). Bostryx conspersus is endemic of the Lomas ecosystem in Peruvian Coastal Desert. In this paper, chromosomes in prophase I of meiosis of spermatocytes Bostryx conspersus are described.